Vocal cord paralysis after endotracheal intubation: an uncommon complication of general anesthesia - Nazal,Claudia Hurtado (2018)
Abstract Background: General anesthesia is a safe, frequent procedure in clinical practice. Although it is very unusual in procedures not related to head and or neck surgery, vocal cord paralysis is a serious and important complication. Incidence has been associated with patient age and comorbidities, as well as the position of the endotracheal tube and cuff. It can become a dangerous scenario because it predisposes aspiration. Objectives: To present a case and analyze the risk factors associated with increased risk of vocal cord paralysis described in the literature. Case report: 53 year-old diabetic man, who developed hoarseness in the postoperative period after receiving general anesthesia for an elective abdominal laparoscopic surgery. Otolaryngological evaluation showed left vocal cord paralysis. Conclusions: Vocal cord paralysis can be a serious complication of general anesthesia because of important voice dysfunction and risk of aspiration. The management is not yet fully established, so prevention and early diagnosis is essential.